2014
DOI: 10.1177/0954406214541797
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of percussion water jets driven by multiple collisions

Abstract: A numerical model is proposed in this research to analyse the behaviour of the pulse jet driven by percussion hammer. The mass of the hammer is usually larger than that of the piston and the resistance of compressed water can low down the piston, thus multiple collisions occur each time when the hammer strikes the piston. The proposed model has the merit to consider various striking possibilities to simulate the process of pulse water jet generated by multiple hammer collisions. In addition, a hammer-driven pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…High-speed photography is a technology that can effectively diagnose and test the jet. Ding et al [17] quantitatively measured the diffusion trajectory of the jet concentration field based on image analysis technology, Li et al [18] observed the change law of jet head penetration velocity into the water protective layer based on flash X-ray photography, Ye Yan et al [19] used high-speed photography and pulse coaxial holography to diagnose the dynamic image of micro jet head, Liu et al [20] used high-speed photography and postprocessing technology to study the spray characteristics of the nozzle plume at different stages, Lu et al [21] used high-speed photography to capture the evolution process of the drop hammer impact pulsed water jet in the flow field, and A. Matthujak et al [22] used aerial photography and shadow technology to visualize the impact-driven high-speed jet. Zdenek Riha et al [23] used photography technology to compare and analyze the structural characteristics of acoustic-wave-excited pulsed water jets and continuous water jets.…”
Section: Introductionmentioning
confidence: 99%
“…High-speed photography is a technology that can effectively diagnose and test the jet. Ding et al [17] quantitatively measured the diffusion trajectory of the jet concentration field based on image analysis technology, Li et al [18] observed the change law of jet head penetration velocity into the water protective layer based on flash X-ray photography, Ye Yan et al [19] used high-speed photography and pulse coaxial holography to diagnose the dynamic image of micro jet head, Liu et al [20] used high-speed photography and postprocessing technology to study the spray characteristics of the nozzle plume at different stages, Lu et al [21] used high-speed photography to capture the evolution process of the drop hammer impact pulsed water jet in the flow field, and A. Matthujak et al [22] used aerial photography and shadow technology to visualize the impact-driven high-speed jet. Zdenek Riha et al [23] used photography technology to compare and analyze the structural characteristics of acoustic-wave-excited pulsed water jets and continuous water jets.…”
Section: Introductionmentioning
confidence: 99%